Detecting Xanthomonas axonopodis pv. manihotis in cassava true seeds by nested polymerase chain reaction assay - Ojeda, S; Verdier, Valerie M. (Informa UK Limited, 2000)
Cassava bacterial blight, caused by Xanthomonas axonopodis pv. manihotis (Xam), is a particularly destructive disease in South America and Africa. Because of quarantine procedures, international exchange of cassava germplasm is limited and occurs through true seeds or material propagated in vitro. The success of a cassava-seed certification program depends on the availability of reliable tests to detect the pathogen in true seeds and vegetative planting materials. We developed a nested polymerase chain reaction assay to detect the pathogen in cassava true seeds. The internal primers directed the amplification of a fragment of 509 base pairs in all 12 Xam strains tested, whereas no amplification product was obtained from any of the 17 strains of other Xanthomonas pathovars tested. Nested polymerase chain reaction worked well for Xam detection from cultured cells from artificially inoculated seeds and naturally infected seeds. The best detection level allowed to detect a presence as low as one to two viable cells per reaction. This technique was specific, sensitive, and rapid for detecting Xam in cassava true seeds.